The effect of individual incentive towards employee performances at Tenaga Nasional Berhad, Batu Gajah, Perak / Muhammad Ramzan Razian - Razian, Muhammad Ramzan (2015)
The purpose of the study is to identify the effect of incentive given towards performance of employees. Another objective is to determine the relationship between the incentives with employee performance. Individual incentive consists of bonus, merit pay, incentive awards and standard hour plan. The data was distributed and collected by 44 employees by using questionnaire and random sampling. The result was held at Tenaga Nasional Berhad, Batu Gajah that involved male and female respondent. Data collection will be analyzed using Statistical Package for Social Science (SPSS, Version 21.0). The results show that there was a relationship for all variables toward job performance. However, the relationship between all variables and job performance is weak. The limitations of study are limited in small area which is Tenaga Nasional Berhad (TNB), Batu Gajah, Perak. The research just involved 44 persons in Finance, Administrative and Customer Service departments. Time to do this researcher also limited that causes the difficulty to collect relevant data.